Open archaeology. Advances and challenges in the management of archaeological contents - Fernández Cacho, Silvia (Complutum, 2021)
During the last two decades there has been a crucial change in the ways of producing, accessing and using information from all branches of knowledge, including archaeology. Concepts such as open data and content, open access, free software, social construction of knowledge, etc. have been installed in the theory and practice of scientific research (open science) and administrative management (open government) to become an outstanding potential vector for the advancement of scientific knowledge, the economy based on use of data and the transparency of institutions. In the field of cultural heritage, the democratization of knowledge, social participation in public management or the rise of cultural tourism, also affect the increasingly close relationship between the academic, professional and administrative fields and these, in turn, with a population that ceases to be exclusively passive recipient of the information filtered from these areas, to become involved in many of the aspects that concern its management. In this context, archaeology shows some singularities that will be discussed in this paper, focusing on the Spanish case. For this purpose, the advances that have taken place in the generation of open archaeological contents will be reviewed, as well as the main remaining challenges.